Dirichlet Solutions of Functional Differential Equations without Delay - N. P. Evlampiev; V. S. Mokeichev; I. E. Filippov (Учёные записки Казанского университета: Серия Физико-математические науки)
Necessary and sufficient conditions for the existence of a valid Dirichlet solution were obtained. A method was developed to find Dirichlet solutions of the functional differential equation with non-delayed linear argument deviation.